2011
DOI: 10.1007/s00775-011-0866-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a carbon monoxide adduct of a heme–DNA complex

Abstract: The structure of a carbon monoxide (CO) adduct of a complex between heme and a parallel G-quadruplex DNA formed from a single repeat sequence of the human telomere, d(TTAGGG), has been characterized using ¹H and ¹³C NMR spectroscopy and density function theory calculations. The study revealed that the heme binds to the 3'-terminal G-quartet of the DNA though a π-π stacking interaction between the porphyrin moiety of the heme and the G-quartet. The π-π stacking interaction between the pseudo-C₂-symmetric heme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(78 citation statements)
references
References 29 publications
2
76
0
Order By: Relevance
“…2.6 ppm of the G4, G5, and G6 NH signals, respectively ( Table 1 (Table 1). 11 In the case of the diamagnetic CO adduct of the heme(Fe 2+ ) DNA complex, the ¦¤ H(II) values observed for the DNA proton signals were attributed primarily to the ring current effect of the porphyrin moiety of heme(Fe 2+ ), and calculation using the reported equation for the ring current effect of a porphyrin, 35 together with a simple model for the DNA structure constructed on the basis of an X-ray crystallographic study of stacked Gquartets, 36 indicated that the heme(Fe 2+ ) located at 0.34 nm from the G6 G-quartet satisfies the ¦¤ H(II) values for the G4, G5, and G6 NH signals (see Figure SI13 in the Supporting Information). Consequently, similarities in the ¦¤ H(II) values for the G4, G5, and G6 NH signals between the heme(Fe 14 a) Shifts of signals, labeled G4(free), G5(free), G6(free) in Figure 7, spectrum B¤, due to the DNA in 50 mM KCl and 50 mM potassium phosphate buffer, pH 7.00, at 25°C.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2.6 ppm of the G4, G5, and G6 NH signals, respectively ( Table 1 (Table 1). 11 In the case of the diamagnetic CO adduct of the heme(Fe 2+ ) DNA complex, the ¦¤ H(II) values observed for the DNA proton signals were attributed primarily to the ring current effect of the porphyrin moiety of heme(Fe 2+ ), and calculation using the reported equation for the ring current effect of a porphyrin, 35 together with a simple model for the DNA structure constructed on the basis of an X-ray crystallographic study of stacked Gquartets, 36 indicated that the heme(Fe 2+ ) located at 0.34 nm from the G6 G-quartet satisfies the ¦¤ H(II) values for the G4, G5, and G6 NH signals (see Figure SI13 in the Supporting Information). Consequently, similarities in the ¦¤ H(II) values for the G4, G5, and G6 NH signals between the heme(Fe 14 a) Shifts of signals, labeled G4(free), G5(free), G6(free) in Figure 7, spectrum B¤, due to the DNA in 50 mM KCl and 50 mM potassium phosphate buffer, pH 7.00, at 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the stacking of the pseudo-C 2 symmetric heme onto the C 4 symmetric G6 G-quartet, the orientation of the porphyrin moiety of the heme relative to the G6 G-quartet depends upon which side of the heme plane, i.e., either the obverse or reverse heme orientation, interacts with the G6 G-quartet, because the steric contacts between heme vinyl side chains and DNA G6 sugars could be slightly altered on the 180°rotation of the pseudo-C 2 symmetric heme around the 5-H15-H axis. 11 The observation of single G6 imino NH proton signals for each of the obverse and reverse heme orientations ( Figure 7B¤) indicated that the time scale of the interconversion among the four optimal orientations of the heme is fast enough to average out the possible shift differences among the four G6 imino NH proton signals of the complex. On the other hand, the small splitting of the G6 NH signal ( Figure 7B¤) indicated that the time scale of the heme flipping on the G6 G-quartet of the complex, i.e., the interconversion between the obverse and reverse heme orientations, is rather slow.…”
Section: +mentioning
confidence: 92%
See 3 more Smart Citations